Two- and Three-Component Visible Light Photoinitiating Systems for Radical Polymerization Based on Onium Salts: An Overview of Mechanistic and Laser Flash Photolysis Studies - María L. Gómez; Carlos M. Previtali; Hernán A. Montejano (International Journal of Photoenergy)
A review of our work on two- and-three component photoinitiator systems is presented. The emphasis is in on visible light polymerization in aqueous media. The systems discussed comprise a synthetic dye as sensitizer and an onium salt as coinitiator, or a dye-amine-onium salt with the amine as coinitiator and the onium salt as an enhancer of the polymerization efficiency. The effect of the composition of the system on the photopolymerization kinetics was analyzed. To this end, the photophysics and photochemistry of the dye under polymerization conditions was explored by means of stationary and time-resolved spectroscopic methods. Different dyes and onium salts were investigated. The action mechanism of the different photoinitiators systems is discussed.